2015
DOI: 10.1177/0265813515624686
|View full text |Cite
|
Sign up to set email alerts
|

The spatial configuration of urban crime environments and statistical modeling

Abstract: The aim of this paper is to discuss the representation of space in statistical models of urban crime. We argue that some important information represented by the properties of space is either lost or hardly interpretable if those properties are not explicitly introduced in the model as regressors. We illustrate the issue commenting on the shortcomings of the two standard approaches to modeling the dispersion of crime in a city: using local attributes of places as regressors, and defining a catch-all spatial co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…This interesting approach provides a new perspective on incidents like predatory crime, arson, or criminal damage, occurring in the open space. The very specific street pattern of the downtown area of Szczecin consisting of many star-shaped places and streets that are often not parallel to each other, may be a good study area for verifying the results obtained by Bella di et al [42,43].…”
Section: Methods and Analysismentioning
confidence: 56%
See 1 more Smart Citation
“…This interesting approach provides a new perspective on incidents like predatory crime, arson, or criminal damage, occurring in the open space. The very specific street pattern of the downtown area of Szczecin consisting of many star-shaped places and streets that are often not parallel to each other, may be a good study area for verifying the results obtained by Bella di et al [42,43].…”
Section: Methods and Analysismentioning
confidence: 56%
“…The results from the POSAC model seem to have the most advantages regarding the requirements of public administration. In another study, Bella di et al [43] develop a set of statistical measures called Median Line Angular Segment Analysis (MLASA) based on the configuration concept of space proposed by Hillier [29]. This interesting approach provides a new perspective on incidents like predatory crime, arson, or criminal damage, occurring in the open space.…”
Section: Methods and Analysismentioning
confidence: 99%
“…Eight sociodemographic variables were tested to account for neighbourhood disadvantage: residential population, five-year residential mobility, percent of immigrant residents, index of ethnic heterogeneity, percent of lone-parent families, percent of low-income families, median income, and percent young adult population (Table 2) (Craglia et al, 2005;Law and Quick, 2013). Residential population was analyzed as an explanatory variable because property crime may be concentrated in small-areas with mostly non-residential land use (i.e., residential population is not a representative population at risk) and because residential population is a proxy for the number of potential offenders in the routine activity theory (di Bella et al, 2015).…”
Section: Study Region and Datamentioning
confidence: 99%
“…Another limitation of the study is that we did not account for the role of the spatial configuration in explaining crime risks. Recent research has shown that spatial configuration can be a substantial factor in creating crime risks and in revealing the sources of spatial autocorrelation in crime data [71].…”
Section: Discussionmentioning
confidence: 99%